Factors influencing college students' purchase intention towards Bamboo textile and apparel products. Issue 1 (2nd January 2016) - Thompson, Amanda; Tong, Xiao
ABSTRACT: This study investigates the factors that might influence American consumers' purchase intention towards bamboo textile and apparel products. Guided by Sproles' fashion adoption theory, a survey was conducted to examine the effects of fashion orientation, shopping orientation, and environmental concern and eco-friendly behaviour on purchase intention of bamboo textile and apparel products. A total of 307 usable questionnaires were collected from young American consumers. Results from structural equation modelling analyses indicated that fashion leadership and environmental concern are significantly related to consumers' purchase intention towards bamboo textile and apparel products.